Implementation of The Certainty Factor Method in The Expert System For Early Diagnosis of Dyslexia in Childhood - Ashidiqi, Ahmad Siroj; Widaningrum, Ida; Karaman, Jamilah (Universitas Nusantara PGRI Kediri, 2023)
Dyslexia is a condition in which a person has difficulty (especially) in areas related to learning abilities such as reading, writing, and arithmetic or matters relating to numbers. This condition is not the skills expected of people with chronological age and normal intelligence abilities or IQ (quality of intelligence). This condition is sometimes not realized by parents and only consider their child slightly delayed, even though it is under standard (minimum) abilities at his age. Therefore, a platform using an expert system with the Certainty Factor method was created to help parents detect early whether their child has dyslexia or not and find out what type of dyslexia the child is experiencing. The types of dyslexia that will be included in this study include surface dyslexia, phonological dyslexia, rapid naming deficit, dysgraphia, and dyscalculia. The white box results found that the system was in line with expectations because it had a low level of risk.